Synthesis and characterization of bioceramic from Malaysian cockle shell - Nur Farahiyah, Mohammad; Muhammad Adam, Zahid; Saidatul Ardeenawatie, Awang; Zulkarnay, Zakaria; Azian Azamimi, Abdullah (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/